PENINGKATAN AKTIVITAS BELAJAR SISWA DALAM MATA PELAJARAN BIOLOGI MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY – TWO STRAY (TS-TS) DI KELAS X.3 SMAN 1 LUHAK NAN DUO - Suhelpi, Suhelpi (STKIP Pesisir Selatan, 2017)
Based on student learning activity Class X.3 SMAN 1 Luhak Nan Duo in Biology Course found that student learning activity in Biology Subject is still very low. The purpose of this research is to describe and get information about Student Activity Improvement in Biology Subjects through Two Stay-Two Stray (TS-TS) cooperative learning model in Class X.3 SMAN 1 Luhak Nan Duo Sub-district of West Pasaman. This study is a classroom action research. The research procedures in this study include planning, action, obeservation and reflection. This study consists of two cycles with four meetings. The subjects consisted of 36 students of Class X.3 of SMAN 1 Luhak Nan Duo. The research data was collected by using observation sheet. Data were analyzed using percentages. Based on the results of research and discussion that have been stated in the previous chapter, it can be concluded that it can be concluded that the two stays two stray (TS-TS) learning model can improve student learning activities in Biologidi SMAN 1 Luhak Nan Duo. Student learning activity in cycle I was 71,77 (enough) increased to 81.62 (good) with an increase of 9.85